URGENSI PEMBELAJARAN MENERJEMAH ARAB-INDONESIA: SEBAGAI ASET DALAM DUNIA BAHASA ARAB - Mohammad Jailani; Alin Hidayati (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Nurul Hakim, 2023)
Translating is translating from one language to another while maintaining the accuracy of both languages in detail. The purpose of this study is to provide insight into the importance of translation as a means of knowledge transfer between different cultures, languages and nations. As an activity to move the message or intent contained in one language into another language appropriately and reasonably. In its preparation, the author uses a qualitative method of literacy studies from journals and articles. Translation skills in the present need to be developed more in students majoring in Arabic language and literature themselves. In line with the development of the times our society requires professional translators in this case Arabic translators.